The Effect of Plyometric Training towards Long Jump of Squat Style Ability on Second Grade Male Students in SMP Negeri 2 Manganitu - Fredrik Alfrets Makadada; Djajaty Mariana Lolowang (BIRCU, 2020)
The aims of the study to find out the extent of the effect of plyometric training on the ability to squat-style long jump on 2th grade male students of SMP Negeri 2 Manganitu. There is an influence of plyometric training on the ability to squat-style long jump in 2th grade male students of SMP Negeri 2 Manganitu. The research method used was an experimental method with treatment in the form of an exercise program given for eight weeks. The population was all male students of 2th grade of SMP Negeri 2 Manganitu amounting to 20 people and a sample of 20 people, then divided into two groups each with 10 experimental groups and 10 control groups. Data collection instruments: Squat-style long jump test. The study design uses: randomized control groups pre-test and post-test design. Hypothesis testing using statistical techniques with t test. The results of hypothesis analysis, obtained t observation of 21.63, while t table obtained from the degree of freedom n-1 + n2 - 2 that is 10 + 10 - 2 = 18 and the level of confidence = 0.05 is 2.10. In accordance with the test criteria accept Ho if t observation is smaller than t table and reject Ho if t observation is greater than t table. Because t observation is greater than t table, the results of the analysis show reject Ho and accept Ha. Conclusion: Pliometric exercises given for eight weeks with a frequency of three times a week can improve the squat-style long jump ability in male students of 2th grade SMP Negeri 2 Manganitu.